Kanca Wingking: reinterpreting the identity of Javanese women through video installation art - Dias Adiprabowo, Vani (Jurnal Studi Komunikasi, 2025)
The identity of Javanese women has long reflected constructions by patriarchal cultural narratives, with the concept of Kanca Wingking confining them to domestic roles and subordinating them to men. This study investigates how video installation art represents and deconstructs that discourse. The research examines how visual, auditory, and interactive elements challenge the gendered symbolic order by employing a qualitative approach that integrates Julia Kristeva's semiotic theory and Foucauldian discourse analysis. The researcher collected data through a literature review and visual documentation of Javanese cultural representations. The findings demonstrate that video installation art not only symbolises patriarchal control, through elements such as the puppeteer's voice and the manipulation of women's expressions, but also subverts it by turning the audience into active participants in exposing and questioning those norms. From a Foucauldian perspective, the work reveals how domestic spaces and bodily representation function as instruments of discipline and surveillance, yet simultaneously open discursive space for agency and resistance. The study concludes that video installation art serves as both an expressive and political medium, offering critical interventions into the cultural construction of Javanese womanhood.